2017
DOI: 10.1016/j.jpain.2017.02.430
|View full text |Cite
|
Sign up to set email alerts
|

Classical Conditioning Differences Associated With Chronic Pain: A Systematic Review

Abstract: The review revealed preliminary evidence that people with chronic pain may exhibit less differential US expectancy and fear learning. This characteristic may contribute to widespread fear-avoidance behavior. The assumption that altered classical conditioning may be a predisposing or maintaining factor for chronic pain remains to be verified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
57
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(64 citation statements)
references
References 45 publications
4
57
0
3
Order By: Relevance
“…It serves to rapidly shift attention toward signals of threat in order to avoid bodily harm, engage in self-protection and seek safety. Although adaptive by nature, fear and ensuing avoidance behaviors can also become maladaptive, with broad implications for the pathophysiology and treatment of chronic pain (1,2). The fear-avoidance model of pain proposes a vicious cycle of pain-related fear, hypervigilance and avoidance, maintained, and modulated by psychological vulnerability factors like anxiety, catastrophizing, and negative affect (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…It serves to rapidly shift attention toward signals of threat in order to avoid bodily harm, engage in self-protection and seek safety. Although adaptive by nature, fear and ensuing avoidance behaviors can also become maladaptive, with broad implications for the pathophysiology and treatment of chronic pain (1,2). The fear-avoidance model of pain proposes a vicious cycle of pain-related fear, hypervigilance and avoidance, maintained, and modulated by psychological vulnerability factors like anxiety, catastrophizing, and negative affect (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…As an evolutionarily well-conserved process, generalization enables safe and efficient navigation of a complex and multidimensional world ( Sutton and Barto, 1998 ; Ghirlanda and Enquist, 2003 ). However, over- generalization, resulting in inappropriate avoidance of safe stimuli, actions or contexts, has been suggested as a possible pathological mechanism in a range of psychological disorders including anxiety, chronic pain, and depression ( Duits et al, 2015 ; Dymond et al, 2015 ; Vlaeyen and Linton, 2012 ; Harvie et al, 2017 ; Pearson et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have suggested that 1) pain-related fear and avoidance appear to be essential features of the development of a chronic pain state in patients with musculoskeletal pain, 21 29 and 2) fear-avoidance beliefs and catastrophizing have been implicated in chronic pain and may interact with the experience of pain. 30 , 31 These studies suggest that it is very important to decrease fear-avoidance beliefs and pain catastrophizing to improve the QOL of patients with chronic musculoskeletal pain.…”
Section: Discussionmentioning
confidence: 99%